PENGARUH KOMBINASI ABU JANJANG KELAPA SAWIT DENGAN PUPUK UREA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DI TANAH GAMBUT - Kristian H, Kristian H; Wardati, Wardati; Rustam, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research is to know the effect of the combination of oil palm bunch ash with urea fertilizer on the growth of cocoa seedlings (Theobroma cacao L.) in peat soil and to know the best dose. This research was conducted in experimental garden of Agricultural Faculty of University of Riau on December 2016 until March 2017. This research method used non factorial Complete Random Design (RAL) consisting of 6 treatments and 3 replications. The treatments consisted of 4 g AJKS + 0.5 g Urea, 4 g AJKS + 1 g Urea, 4 g AJKS + 2 g Urea, 8 g AJKS + 0.5 g Urea, 8 g AJKS + 1 g Urea and 8 g AJKS + 2 g Urea. Parameters observed were; plant height, number of leaves, stem diameter, leaf area, root volume, ratio root crown and dry weight of cocoa seedlings. The data obtained were analyzed statistically by using vocabulary and then tested further with DNMRT test at 5% level. The combination of AJKS with urea fertilizer in peat soil significantly affected the diameter of stem, root volume. However, the effect was not significant on plant height, number of leaves, stem diameter, leaf area, ratio root crown and dry weight of cocoa seedlings. The results of this study indicate that giving AJKS combination with urea fertilizer with dose 8 g AJKS + 2 g urea in peat soil produces the best growth of cocoa seedlings.Â Keywords : Oil palm bunch ash, Urea fertilizer, Peat soil, Cocoa